(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract. Introduction. The article examines the economic concept of «price», «marketing pricing policy» and its interpretation by various domestic and foreign scientists. The process of the marketing policy of the enterprise’s pricing and the use of various concepts of pricing, the choice of which depends on the characteristics of the product or service and the marketing goals of the enterprise, have been studied. Research in relation to a marketing pricing of enterprise policy is actual, as it will allow to decide the row of urgent problems, in particular, establishment of optimal price on products, increase of volumes of sales, increase of level of satisfaction of consumers and other and is especially appropriate in the conditions of strengthening of competition and introduction of new technologies in economic activity. The purpose of the article. Research of essence, maintenance and role of marketing pricing policy. Aims that can be attained by means of effective pricing policy. Metods. During research the methods of comparison, analysis, synthesis, abstraction, theoretical, historical and logical generalization are used. The dialectical method of research became methodological basis. Results. The essence of the economic concept "price", "marketing pricing policy" is revealed. It has been studied that the marketing policy of pricing is an important component of the company’s marketing strategy. Formation of prices for goods and services requires the company to carefully analyze the market, competitors, consumers and own costs, and the main goal of pricing is to achieve maximum profit for the company. Conclusiоns. The analysis of the theoretical and practical aspects of marketing pricing policy showed the place and role that pricing policy plays in achieving strategic goals and ensuring the sustainable development of the enterprise, analyzed the main approaches to pricing and identified a number of factors affecting the choice of pricing strategy. It has been studied that in the process of marketing pricing policy, enterprises can use various concepts of pricing, such as price elasticity, competitiveness, consumer orientation and others. The choice of the pricing concept should depend on the characteristics of the product or service, as well as on the marketing goals of the enterprise. Further research is seen appropriate to point at sound determination of marketing strategies of companies of different patterns of ownership.